2017
DOI: 10.1515/nuka-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

57Fe Mössbauer spectroscopy investigations of iron phase composition in fluidized beds from the ELCHO power plant in Chorzów, Poland

Abstract: Abstract. The study investigates the physical and chemical properties of fl y ash and bottom ash from a power plant ELCHO in Chorzów, Poland. Coal combustion products generated in the process of combustion in circulating fl uidized beds (CFBs) are considerably different from fl y and bottom ashes obtained from dust furnaces and multi-layer ones. The composition of the iron-bearing phase in the waste of circulating fl uidized bed combustion was determined using Mössbauer spectroscopy and X-ray powder diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…The Z1 component with a hyperfine magnetic field value of 51 T was identified as hematite with a stable share in the sample (19%). Similar results of Mössbauer spectroscopy were obtained for fly and bottom ashes generated in fluidized bed boilers in a Silesian power plant [ 34 ]. In fly ash samples, Waanders et al found the presence of hematite and compounds with Fe 3+ ions, as well as amorphous Fe 3+ , in glass and muscovite [ 35 ].…”
Section: Resultssupporting
confidence: 75%
“…The Z1 component with a hyperfine magnetic field value of 51 T was identified as hematite with a stable share in the sample (19%). Similar results of Mössbauer spectroscopy were obtained for fly and bottom ashes generated in fluidized bed boilers in a Silesian power plant [ 34 ]. In fly ash samples, Waanders et al found the presence of hematite and compounds with Fe 3+ ions, as well as amorphous Fe 3+ , in glass and muscovite [ 35 ].…”
Section: Resultssupporting
confidence: 75%
“…These two samples contain a small part of iron located in nonmagnetic iron oxide like wüstite. Paramagnetic ferric doublet observed on these spectra with isomer shift of about 0.20 mm/s and average quadrupole splitting of about 0.44 mm/s probably corresponds to amorphous Fe 3+ in glass, which was suggested by other authors [7][8][9].…”
Section: Resultssupporting
confidence: 65%
“…After annealing process no significant changes of the hyperfine parameters of this doublet were observed, each time they remained in the ranges presented above, only contributions of this doublet changed much with the increase in temperature. Except the main doublet on the Mössbauer spectrum there is another one with I s = 0.183 mm/s and Q s = 0.475 mm/s visible, which is connected with Fe 3+ in quartz structure [13]. A sextet with hyperfine magnetic field B = 35.8 T, I s = 0.355 mm/s is related to the presence of chalcopyrite in the investigated sample.…”
Section: Resultsmentioning
confidence: 79%